Transcriptomic analysis of mouse liver reveals a potential hepato-enteric pathogenic mechanism in acute Toxoplasma gondii infection - He, Jun-Jun; Ma, Jun; Elsheikha, Hany M.; Song, Hui-Qun; Huang, Si-Yang; Zhu, Xing-Quan (BioMed Central, 2016)
Background